2015
DOI: 10.1016/j.apcata.2015.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of HMF hydrodeoxygenation over different metal catalysts in a continuous flow reactor

Abstract: The three-phase hydrodeoxygenation (HDO) of 5-hydroxymethylfurfural (HMF) and hydrogenation of 2,5-dimethylfuran (DMF) were studied over six carbon-supported metal catalysts (Pt, Pd, Ir, Ru, Ni, and Co) using a tubular flow reactor with 1-propanol solvent, at 180°C and 33 bar. By varying the space time in the reactor, the reaction of HMF is shown to be sequential, with HMF reacting first to furfuryl ethers and other partially hydrogenated products, which then form 2,5-dimethylfuran (DMF). Ring-opened products … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 17 publications
2
65
0
Order By: Relevance
“…The 10-wt% Ni/C, Co/C, Cu/C and Zn/C catalyst in this study were prepared by impregnation, using an identical procedure that is consistent with those in previous studies [8].…”
Section: Synthesis Of Conventional Ni/c Co/c Cu/c and Zn/c Catalystsmentioning
confidence: 95%
See 4 more Smart Citations
“…The 10-wt% Ni/C, Co/C, Cu/C and Zn/C catalyst in this study were prepared by impregnation, using an identical procedure that is consistent with those in previous studies [8].…”
Section: Synthesis Of Conventional Ni/c Co/c Cu/c and Zn/c Catalystsmentioning
confidence: 95%
“…In previous studies, we showed that the HDO reaction for HMF in several alcohol solvents is a series reaction, with products forming as shown in Scheme 1 [8,22]. The HMF (A)…”
Section: Hydrodeoxygenation Of Hmf In a Continuous Flow Reactormentioning
confidence: 98%
See 3 more Smart Citations